XUV pump–XUV probe transient absorption spectroscopy at FELs. (12th February 2021) - Ding, Thomas; Rebholz, Marc; Aufleger, Lennart; Hartmann, Maximilian; Stooß, Veit; Magunia, Alexander; Birk, Paul; Borisova, Gergana Dimitrova; da Costa Castanheira, Carina; Rupprecht, Patrick; Mi, Yonghao; Gaumnitz, Thomas; et al.
Abstract : A setup for an all-XUV transient absorption spectroscopy at free-electron lasers, was developed and employed to explore XUV-excited dynamics and XUV-driven nonlinear phenomena. Abstract : The emergence of ultra-intense extreme-ultraviolet (XUV) and X-ray free-electron lasers (FELs) has opened the door for the experimental realization of non-linear XUV and X-ray spectroscopy techniques. Here we demonstrate an experimental setup for an all-XUV transient absorption spectroscopy method for gas-phase targets at the FEL. The setup combines a high spectral resolving power of E /Δ E ≈ 1500 with sub-femtosecond interferometric resolution, and covers a broad XUV photon-energy range between approximately 20 and 110 eV. We demonstrate the feasibility of this setup firstly on a neon target. Here, we intensity- and time-resolve key aspects of non-linear XUV-FEL light–matter interactions, namely the non-resonant ionization dynamics and resonant coupling dynamics of bound states, including XUV-induced Stark shifts of energy levels. Secondly, we show that this setup is capable of tracking the XUV-initiated dissociation dynamics of small molecular targets (oxygen and diiodomethane) with site-specific resolution, by measuring the XUV transient absorption spectrum. In general, benefitting from a single-shot detection capability, we show that the setup and method provides single-shot phase-locked XUV pulse pairs. This lays the foundation to perform, in the future, experiments as a function of the XUV interferometric time delay and the relative phase, which enables advanced coherent non-linear spectroscopy schemes in the XUV and X-ray spectral range.